The Development of Children's Giftedness in Creative Self-Realization: Conceptual Thesis - Yu. Kozlova, Anna; N. Samsonova, Asya; Yu. Tumanov, Dmitriy; Thanh Nguyen, Phong; Le Hoang Thuy To Nguyen, Quyen; Bich Huynh, Vy Dang (International Journal of Psychosocial Rehabilitation, 2024)
The dynamics of modern society determines the need for creatively gifted people. Based on the request and the value needs of society, the goal of spiritual and creative development of a gifted person is formulated - this is the development of the person’s ability to choose moral values independently, the creation of a creative field for creative self-development and self-realization, focused on the reflection of moral criteria, the creative process and product based on humanistic ideals. Conceptual provisions involve the identification of patterns and principles of the development of giftedness in the creative self-realization of preschool children. The analysis of the socio-educational space of the pedagogical strategy for the development of gifted children allowed the authors to determine the methodological basis: the sociocultural approach to the education of a preschool child; a phenomenological approach in considering the phenomenon of giftedness; a synergistic approach that ensures the self-realization of a gifted person in creative activity; axiological approach in considering the basics of self-realization of a gifted person; theory of personality-oriented approach in preschool education; creative-activity approach in the education of gifted preschool children. The indicated methodological approaches determined the basic laws and principles of the development of preschool children giftedness in a creative educational space. The article discloses the concept of the development of preschool children giftedness in creative self-realization through the substantiation of patterns in psychological and pedagogical principles